Novel Biomarkers of Endothelial Dysfunction in Cardiovascular Diseases - Z. M. Abdurakhmanov; B. Y. Umarov; M. M. Abdurakhmanov (Столичная издательская компания, 2021)
The review analyzes the role of assessing the state of the endothelium in the onset and progression of cardiovascular diseases, stratification of their risks, since endothelial dysfunction (ED) is a crucial predictor of this pathologies. In this regard, this paper presents the modern understanding of the methods for assessing ED, presents the advantages and disadvantages of various techniques. Despite the fact that flow-mediated dilation is widely used as a classical method for studying endothelial function, this technique depends on the physiological state of sensory nerves and calcium-activated potassium channels, cardiac output. This review focuses on new biomarkers for ED such as endothelial microparticles, endoglin and endocan, and discusses the relevance of the criteria for their use in clinical practice. Based on current scientific advances, the authors concluded that among these three newest biomarkers, today, endocan can be considered a more informative and reliable cellular marker of ED. Moreover, the authors have shown that when measured separately, many of the studied classical circulating biomarkers do not provide reliable information about the state of the endothelium, since the endothelial function has a complex physiological nature which therefore raises the question of the advisability of considering a combination of classical and new biomarkers for improving the assessment of the endothelial state.